2019
DOI: 10.1155/2019/9647539
|View full text |Cite
|
Sign up to set email alerts
|

UAV-Enabled Data Collection: Multiple Access, Trajectory Optimization, and Energy Trade-Off

Abstract: In this paper, we consider a ground terminal (GT) to an unmanned aerial vehicle (UAV) wireless communication system where data from GTs are collected by an unmanned aerial vehicle. We propose to use the ground terminal-UAV (G-U) region for the energy consumption model. In particular, to fulfill the data collection task with a minimum energy both of the GTs and UAV, an algorithm that combines optimal trajectory design and resource allocation scheme is proposed which is supposed to solve the optimization problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In this paper, we consider the case that there are no direct links between the UE and the BS owing to the long distances and blockages between them. Similar to [9,13,14,20,21], we assume the air-ground wireless channels are dominated by LoS links. e channel power gains from the UAV to the ground BS and from the UAV to the UE n, n ∈ N at time slot t, t ∈ T are, respectively, given as…”
Section: Channel Modelmentioning
confidence: 99%
“…In this paper, we consider the case that there are no direct links between the UE and the BS owing to the long distances and blockages between them. Similar to [9,13,14,20,21], we assume the air-ground wireless channels are dominated by LoS links. e channel power gains from the UAV to the ground BS and from the UAV to the UE n, n ∈ N at time slot t, t ∈ T are, respectively, given as…”
Section: Channel Modelmentioning
confidence: 99%
“…In the paper, the authors evaluated the impact of the UAV trajectory, the direction of the landing approach relative to radio beacons, and the temporal window of the signal analysis on the accuracy of the developed procedure. They indicated that the navigation error near the destination landing point is less than 1 m. In [17], an algorithm that combines optimal trajectory design and resource allocation scheme for multiple ground terminals with UAV arbitrary flight using the successive convex optimization and Lagrange duality is developed. The simulation results proved an increase in energy efficiency compared with the scheme without optimizing trajectory.…”
Section: Cargo Transport Levelmentioning
confidence: 99%
“…The remarkable recent developments in drone technology have provided the opportunity to broadly deploy UAVs for wireless communication purposes, like aircraft, small aircraft, airships, and balloons. [21][22][23] The motivation behind this contribution is that in critical situations, drones can effectively deliver secure and low-cost solutions to the wireless network for a range of real-life situations when adequately deployed and operated. Given these exciting prospects for UAVs, several technical challenges need to be tackled and used effectively for each specific networking application.…”
Section: Motivations and Principal Contributionsmentioning
confidence: 99%